Smart Classroom for Teaching Learning at Secondary Level in West Bengal: An Exploratory Study - Sethy, Rasmirekha; Mohalik, Ramakanta (American Journal of Social Sciences and Humanities, 2019)
The objectives of this paper are to study the availability of equipments and softwares in smart clasrrom and to find out the ICT training of teachers and use of different educational applications by teachers in teaching. Survey method was used with sample of 25 secondary schools selected from three districts (Darjeeling, Hooghly and Siliguri) of West Bengal, India randomly. Self developed and validated questionnaire consisting of 40 items based on availability of equipments, softwares, training of teachers and use of educational applications etc were used as tool for collecting data from school principals. The data were analyzed in terms of frequency count, percentage and average followed by qualitative descriptions. The study indicated that all secondary schools have desktop and projectors in smart classroom but 88% of schools do not have laptop and no schools have interactive board which is important for smart classroom. Half of the teachers are trained in using smart class and ICT for taking class and few schools have subject specific educational softwares. Majority of teachers does not use smart classroom every day for teaching learning. The study suggested that all schools must be equippied with proper digital devices and subject specific softwares. Teachers must be oriented or trained in smart class pedagogy for taking class as it fosters students cognitive capacities. Further, teachers must be encouraged and motivated by educational authority and school principal for using smart classroom facilities in regular teaching activities.